A STUDY ON THE PERCEPTION OF MARKETING MANAGERS IN EMPLOYING ARTIFICIAL INTELLIGENCE FOR SALES AND MARKETING - Mohanan, Manimaran (Digital Repository of Theses - SSBM Geneva, 2023)
This study examines the issues swaying marketing managers' behavioral intention to adopt artificial intelligence (AI) in sales and marketing. Through a comprehensive investigation, the study identified performance expectancy, effort expectancy, and peer influence as the key predictors affecting marketing managers' intentions to use AI-driven tools. The research also considered individual, organizational, and technological factors that could influence these predictors. The findings suggest that organizations should focus on addressing these factors to facilitate successful AI adoption in sales and marketing. This includes providing training and education, ensuring management support, fostering a culture of innovation, and implementing effective change management strategies. Additionally, organizations should invest in developing user-friendly, reliable, compatible, and customizable AI tools, while ensuring robust data management practices. The study provides valuable insights for organizations seeking to harness the power of AI to transform their marketing and sales processes. By understanding the factors influencing marketing managers' intentions and addressing the identified challenges, organizations can successfully integrate AI, stay competitive, and achieve better results in an increasingly dynamic and data-driven marketplace. Future research could explore additional factors, the actual implementation process, and measurable outcomes of AI adoption in sales and marketing to provide more comprehensive and actionable insights.